Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To evaluate the limit [tex]\(\lim_{x \rightarrow 0} \frac{x \cos(x) - \sin(x)}{4 x^3}\)[/tex], we follow a step-by-step approach.
Step 1: Analyze the function
We start with the function:
[tex]\[ f(x) = \frac{x \cos(x) - \sin(x)}{4 x^3} \][/tex]
Step 2: Direct substitution
If we substitute [tex]\(x = 0\)[/tex] directly into the function, we get an indeterminate form [tex]\( \frac{0}{0} \)[/tex]. Hence, direct substitution doesn't help, and we need to apply L'Hospital's Rule.
Step 3: Applying L'Hospital's Rule
L'Hospital's Rule states that for limits of the form [tex]\(\frac{0}{0}\)[/tex] or [tex]\(\frac{\infty}{\infty}\)[/tex], we can compute the limit of the ratio of the derivatives:
[tex]\[ \lim_{x \to 0} \frac{f(x)}{g(x)} = \lim_{x \to 0} \frac{f'(x)}{g'(x)} \][/tex]
In our function:
[tex]\[ f(x) = x \cos(x) - \sin(x) \][/tex]
[tex]\[ g(x) = 4 x^3 \][/tex]
First, we find the derivatives of [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ f'(x) = \frac{d}{dx} (x \cos(x) - \sin(x)) \][/tex]
[tex]\[ g'(x) = \frac{d}{dx} (4 x^3) \][/tex]
Step 4: Calculating the derivatives
- Derivative of [tex]\(f(x)\)[/tex]:
[tex]\[ f'(x) = \frac{d}{dx} (x \cos(x) - \sin(x)) \][/tex]
Using the product rule and chain rule:
[tex]\[ f'(x) = \frac{d}{dx} (x \cos(x)) - \frac{d}{dx} (\sin(x)) \][/tex]
[tex]\[ f'(x) = (\cos(x) - x \sin(x)) - \cos(x) \][/tex]
[tex]\[ f'(x) = \cos(x) - x \sin(x) - \cos(x) \][/tex]
[tex]\[ f'(x) = -x \sin(x) \][/tex]
- Derivative of [tex]\(g(x)\)[/tex]:
[tex]\[ g'(x) = \frac{d}{dx} (4 x^3) \][/tex]
[tex]\[ g'(x) = 12 x^2 \][/tex]
Step 5: Applying L'Hospital's Rule
Now, apply L'Hospital's Rule:
[tex]\[ \lim_{x \to 0} \frac{x \cos(x) - \sin(x)}{4 x^3} = \lim_{x \to 0} \frac{-x \sin(x)}{12 x^2} \][/tex]
Simplify the expression:
[tex]\[ \lim_{x \to 0} \frac{-x \sin(x)}{12 x^2} = \lim_{x \to 0} \frac{- \sin(x)}{12 x} \][/tex]
This again gives an indeterminate form [tex]\( \frac{0}{0} \)[/tex], so we apply L'Hospital's Rule a second time:
Step 6: Second application of L'Hospital's Rule
Taking derivatives again, we get:
[tex]\[ f''(x) = \frac{d}{dx} (- \sin(x)) = - \cos(x) \][/tex]
[tex]\[ g''(x) = \frac{d}{dx} (12 x) = 12 \][/tex]
So,
[tex]\[ \lim_{x \to 0} \frac{- \sin(x)}{12 x} = \lim_{x \to 0} \frac{- \cos(x)}{12} \][/tex]
Substituting [tex]\(x = 0\)[/tex]:
[tex]\[ \lim_{x \to 0} \frac{- \cos(x)}{12} = \frac{- \cos(0)}{12} = \frac{- 1}{12} \][/tex]
Therefore, the limit evaluates to:
[tex]\[ \lim_{x \rightarrow 0} \frac{x \cos(x) - \sin(x)}{4 x^3} = -\frac{1}{12} \][/tex]
Thus, the final answer is: [tex]\(\boxed{-\frac{1}{12}}\)[/tex].
Step 1: Analyze the function
We start with the function:
[tex]\[ f(x) = \frac{x \cos(x) - \sin(x)}{4 x^3} \][/tex]
Step 2: Direct substitution
If we substitute [tex]\(x = 0\)[/tex] directly into the function, we get an indeterminate form [tex]\( \frac{0}{0} \)[/tex]. Hence, direct substitution doesn't help, and we need to apply L'Hospital's Rule.
Step 3: Applying L'Hospital's Rule
L'Hospital's Rule states that for limits of the form [tex]\(\frac{0}{0}\)[/tex] or [tex]\(\frac{\infty}{\infty}\)[/tex], we can compute the limit of the ratio of the derivatives:
[tex]\[ \lim_{x \to 0} \frac{f(x)}{g(x)} = \lim_{x \to 0} \frac{f'(x)}{g'(x)} \][/tex]
In our function:
[tex]\[ f(x) = x \cos(x) - \sin(x) \][/tex]
[tex]\[ g(x) = 4 x^3 \][/tex]
First, we find the derivatives of [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ f'(x) = \frac{d}{dx} (x \cos(x) - \sin(x)) \][/tex]
[tex]\[ g'(x) = \frac{d}{dx} (4 x^3) \][/tex]
Step 4: Calculating the derivatives
- Derivative of [tex]\(f(x)\)[/tex]:
[tex]\[ f'(x) = \frac{d}{dx} (x \cos(x) - \sin(x)) \][/tex]
Using the product rule and chain rule:
[tex]\[ f'(x) = \frac{d}{dx} (x \cos(x)) - \frac{d}{dx} (\sin(x)) \][/tex]
[tex]\[ f'(x) = (\cos(x) - x \sin(x)) - \cos(x) \][/tex]
[tex]\[ f'(x) = \cos(x) - x \sin(x) - \cos(x) \][/tex]
[tex]\[ f'(x) = -x \sin(x) \][/tex]
- Derivative of [tex]\(g(x)\)[/tex]:
[tex]\[ g'(x) = \frac{d}{dx} (4 x^3) \][/tex]
[tex]\[ g'(x) = 12 x^2 \][/tex]
Step 5: Applying L'Hospital's Rule
Now, apply L'Hospital's Rule:
[tex]\[ \lim_{x \to 0} \frac{x \cos(x) - \sin(x)}{4 x^3} = \lim_{x \to 0} \frac{-x \sin(x)}{12 x^2} \][/tex]
Simplify the expression:
[tex]\[ \lim_{x \to 0} \frac{-x \sin(x)}{12 x^2} = \lim_{x \to 0} \frac{- \sin(x)}{12 x} \][/tex]
This again gives an indeterminate form [tex]\( \frac{0}{0} \)[/tex], so we apply L'Hospital's Rule a second time:
Step 6: Second application of L'Hospital's Rule
Taking derivatives again, we get:
[tex]\[ f''(x) = \frac{d}{dx} (- \sin(x)) = - \cos(x) \][/tex]
[tex]\[ g''(x) = \frac{d}{dx} (12 x) = 12 \][/tex]
So,
[tex]\[ \lim_{x \to 0} \frac{- \sin(x)}{12 x} = \lim_{x \to 0} \frac{- \cos(x)}{12} \][/tex]
Substituting [tex]\(x = 0\)[/tex]:
[tex]\[ \lim_{x \to 0} \frac{- \cos(x)}{12} = \frac{- \cos(0)}{12} = \frac{- 1}{12} \][/tex]
Therefore, the limit evaluates to:
[tex]\[ \lim_{x \rightarrow 0} \frac{x \cos(x) - \sin(x)}{4 x^3} = -\frac{1}{12} \][/tex]
Thus, the final answer is: [tex]\(\boxed{-\frac{1}{12}}\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.